2007
DOI: 10.1080/02687030701192448
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction as an explanatory basis for conversation symptoms of aphasia: A pilot study

Abstract: Background: Lack of communicative success for people with aphasia is no longer seen as purely a linguistic deficit. Instead, the integrity of the executive functions (EF) is thought to be at least partly responsible for successful communication, particularly during conversation. In order to inform clinicians regarding both conversation and EF, a merging of two paradigms-conversational and neuropsychological approaches-is proposed. Aims: First, we explore the relevance of both neuropsychological and conversatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 21 publications
1
32
0
2
Order By: Relevance
“…Studies have demonstrated that higher order cognitive skills, including executive 5 function, are important to be able to navigate the complex dynamics of human 6 communication (Frankel, Penn, & Ormond-Brown, 2007;Fridriksson et al, 2006;Purdy, 7 2002). Furthermore, previous research suggests that executive function plays an important 8 role in the acquisition and maintenance of anomia therapy gains (Fillingham et al, 2005b;9 Lambon Ralph et al, 2010;Yeung & Law, 2010).…”
Section: Executive Functionmentioning
confidence: 99%
“…Studies have demonstrated that higher order cognitive skills, including executive 5 function, are important to be able to navigate the complex dynamics of human 6 communication (Frankel, Penn, & Ormond-Brown, 2007;Fridriksson et al, 2006;Purdy, 7 2002). Furthermore, previous research suggests that executive function plays an important 8 role in the acquisition and maintenance of anomia therapy gains (Fillingham et al, 2005b;9 Lambon Ralph et al, 2010;Yeung & Law, 2010).…”
Section: Executive Functionmentioning
confidence: 99%
“…Studies have demonstrated that higher order cognitive skills, including executive function, are important to be able to navigate the complex dynamics of human communication (Frankel, Penn, & Ormond-Brown, 2007;Fridriksson et al, 2006;Purdy, 2002).…”
Section: Executive Functionmentioning
confidence: 99%
“…Up to 70% of stroke survivors experience cognitive impairments (Lindén, Skoog, Fagerberg, Steen, & Blomstrand, 2004). The post-stroke cognitive profile is heterogeneous and often involves multiple interconnected cognitive processes, including attention, memory, language, executive functioning and visuospatial skills (Frankel, Penn, & Ormond-Brown, 2007;Fucetola, Connor, Strube, & Corbetta, 2009). In a populationbased study, Barker-Collo and Feigin (2006) examined the association between domain specific deficits in cognition and a range of functional outcomes at five years post-stroke.…”
Section: Background and Current Gap In Research And Clinical Practicementioning
confidence: 99%
“…Cognitive impairments commonly comprise multiple interconnected processes, including attention, memory, language, visuospatial and executive skills (Frankel et al, 2007;Fucetola et al, 2009). Measuring cognitive processes and generating cognitive profiles to understand functional cognitive behaviour are needed to guide rehabilitation.…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation